Comparative evaluation of serum heat shock protein 60 in chronic periodontitis patients with and without coronary heart disease - A case–control study - Anjhana Asok; Rahul Bhandary; Mamatha Shekar Shetty; Amitha Ramesh; Geethu Venugopalan; S Sai Sreeja (Journal of Indian Society of Periodontology)
Background: Heat shock proteins (HSPs) are a group of stress proteins that participate in physiological processes such as cellular folding, assembly, translocation of polypeptides across membranes, and protein repair after cell damage. HSP60 has been implicated in the pathogenesis of both chronic periodontitis (CP) and coronary heart disease (CHD). Aim: The aim was to assess the possible link between CP and CHD by estimating and comparing the serum HSP60 levels in patients with CP with and without CHD. Settings and Design: Ninety patients in the age group of 30–60 years were involved in this study. The patients were categorized as CP (control group) and CP with CHD (case group). Materials and Methods: Gingival index (GI) and periodontal parameters such as probing pocket depth and clinical attachment levels were documented. Enzyme-linked immunosorbent assay was used to determine the HSP60 levels in serum samples obtained from the patients. Statistical Analysis: Results were statistically analyzed using the SPSS version 16.0 software to estimate the mean and standard deviation using independent t-test and Mann–Whitney U-test. Results: The findings of the research indicated that patients with CP with CHD exhibited elevated serum HSP60 levels compared to CP without CHD (P < 0.05). In addition, a statistically significant rise in GI was noted in the case group. However, the periodontal measurements did not reveal any significant differences. Conclusion: As a result, HSP60 levels were observed to be elevated in the case group compared to the control group. Consequently, there is a connection between periodontal disease and CHD that contributes to the overall inflammatory burden.